2011
DOI: 10.5713/ajas.2011.10081
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Carcass Characteristics and Meat Quality of Boer-Cross Wether and Buck Goats Grazing Marshall Ryegrass

Abstract: An experiment was conducted to evaluate the effects of castration on growth performance, carcass characteristics, and meat quality of goat kids. Fourteen Boer-cross buck and wether goat kids (n = 7; initial body weight (BW) 38.0±0.35 kg and 34.8± 0.35 kg, for bucks and wethers, respectively) were grazed on annual Marshall ryegrass (Lolium multiflorum Lam.) for 56 days. Body weights were recorded after 4 h withdrawal from feed and water for two consecutive days, every 2 wk. After d 56, animals were harvested an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
5
13
1
2
Order By: Relevance
“…CLL varied from 2.93 to 3.39% and had no effect (P>0.05) of glycerin levels in the diet; the values are similar to those mentioned by SOLAIMAN et al (2011), reported for grazing crossbred Boer goats, castrated and uncastrated, values of 4.00 and 3.00%, respectively. According to LAGE et al (2009), the CLL of a carcass is an important parameter to assess quality of the product and presents inverse relationship with the juiciness and softness of the meat.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…CLL varied from 2.93 to 3.39% and had no effect (P>0.05) of glycerin levels in the diet; the values are similar to those mentioned by SOLAIMAN et al (2011), reported for grazing crossbred Boer goats, castrated and uncastrated, values of 4.00 and 3.00%, respectively. According to LAGE et al (2009), the CLL of a carcass is an important parameter to assess quality of the product and presents inverse relationship with the juiciness and softness of the meat.…”
Section: Resultssupporting
confidence: 74%
“…HCY varied from 47.60 to 49.39%, and CCY varied from 46.17 to 47.90%, valued within the rate of those described in the literature (CUNHA et al, 2002;EL-WAZIRY et al, 2011;SOLAIMAN et al, 2011;SALLES et al, 2013).…”
Section: Resultsmentioning
confidence: 60%
“…Twenty-four hours after slaughter, the pH value decreased and ranged from 5.5 to 5.7 (pH 24 ). This range of the ultimate pH value is considered to be acceptable for high quality goat meat (5.5-5.8) (Herold et al, 2007;Solaiman et al, 2011). We found that the changes of meat pH and EC recorded for different genotypes had a similar scheme.…”
Section: The Ph and Ecsupporting
confidence: 52%
“…Produksi daging (karkas) merupakan indeks ekonomi yang penting dan berkaitan dengan bobot hidup (bobot potong). Produksi daging akan berubah dari ternak muda sampai ternak dewasa (Kebede et al, 2008;Marichal et al, 2003;Ermias dan Rege, 2003) dan dipengaruhi oleh beragam faktor seperti: bangsa dan jenis ternak (Herold et al, 2007;Santos et al, 2007;Lewis et al, 2004;Ermias dan Rege, 2003;Amin et al, 2000;Singh et al, 1994), jenis kelamin (Solaiman et al, 2011;Peña et al, 2007;Simela et al, 2004;Hall et al, 2001;Abebe, 2000), pakan (Todaro et al, 2006;Lewis et al, 2004;Mahgoub et al, 2000;Meneses et al, 2001;Shahjalal, 2000), serta bobot tubuh dan umur (Abebe, 2000). Penelitian ini bertujuan untuk memprediksi bobot dan konformasi karkas kambing lokal mengunakan prediktor bobot potong dengan pendekatan berbagai model regresi.…”
unclassified